KARAKTERISTIK ARSITEKTUR DESA MEKARWANGI, CISAUK - Danang Harito Wibowo; Muhammar Khamdevi (NALARs, 2017)
Mekarwangi Village is in Banten Province area. It has its own architectural uniqueness, which distincts from Baduy and Java-Banten. However, its uniqueness became faded and abandoned. The Mekarwangi people started to adopt western buildings. On the other hand, most of the area became formal and modern housing development of Serpong. Conservation effort should be initiated, by starting a study about its architectural characteristics. How is the characteristics of the traditional architecture in Desa Mekarwangi? This study is a qualitative research, which is aimed to study the architectural characteristics in Desa Mekarwangi. The results showed, that the stylistic, spatial, physics and figural quality characters is sunda and banten.Keywords: traditional architecture, vernacular, conservation, cultural landscape heritage, local wisdom